Air Tamponade for Rhegmatogenous Retinal Detachment With Inferior Breaks After 25-Gauge Pars Plana Vitrectomy: Technique and Outcome - Shen, Peiyang; Kong, Xiangbin; Zhou, Lijun; Su, Peng; Lu, Xiaohe; He, Mingguang (Frontiers in Medicine, 2022)
To evaluate the outcomes of 25-guage (G) pars plana vitrectomy (PPV) with air tamponade for rhegmatogenous retinal detachment (RRD) with inferior breaks. This retrospective consecutive case series included fifty-two eyes of fifty-two RRD patients with inferior breaks who underwent 25-G PPV with air tamponade. These patients were followed up for at least six months following surgery. Primary and final anatomical success rates and postoperative complications were the main outcome measures. The mean age of the patients (39 men and 13 women) was 51.8 ± 11.8 years. There were 49 primary RRDs (94.2%) and 3 recurrent RRDs (5.8%). The mean follow-up period was 8.2 ± 1.6 months (range: 6-13 months). Sixteen eyes (30.8%) presented with high myopia, and six eyes (11.5%) were pseudophakic. Proliferative vitreous retinopathy grade was C1 in 4 eyes (7.7%). Of the 52 eyes, two (3.8%) were complicated with choroidal detachment, and forty (76.9%) had the macula detached. The single- and final-operation success rates were 96.2% and 100%, respectively. During follow-up, secondary cataract surgery was performed in eight eyes (17.4%) of the 46 phakic eyes. 25-G PPV with air tamponade is effective in treating selected RRD patients with inferior breaks. Patients can benefit from early visual recovery and less complications.